Similar in vitro effects and pulp regeneration in ectopic tooth transplantation by basic fibroblast growth factor and granulocyte‐colony stimulating factor. (25th March 2014) - Takeuchi, N; Hayashi, Y; Murakami, M; Alvarez, FJ; Horibe, H; Iohara, K; Nakata, K; Nakamura, H; Nakashima, M
Abstract : Objectives: Granulocyte‐colony stimulating factor (G‐CSF) has been shown to have combinatorial trophic effects with dental pulp stem cells for pulp regeneration. The aim of this investigation is to examine the effects of basic fibroblast growth factor (bFGF) in vitro and in vivo compared with those of G‐CSF and to assess the potential utility of bFGF as an alternative to G‐CSF for pulp regeneration. Materials and methods: Five different types of cells were examined in the in vitro effects of bFGF on cell migration, proliferation, anti‐apoptosis, neurite outgrowth, angiogenesis, and odontogenesis compared with those of G‐CSF. The in vivo regenerative potential of pulp tissue including vasculogenesis and odontoblastic differentiation was also compared using an ectopic tooth transplantation model. Results: Basic fibroblast growth factor was similar to G‐CSF in high migration, proliferation and anti‐apoptotic effects and angiogenic and neurite outgrowth stimulatory activities in vitro . There was no significant difference between bFGF and G‐CSF in the regenerative potential in vivo . Conclusions: The potential utility of bFGF for pulp regeneration is demonstrated as a homing/migration factor similar to the influence of G‐CSF.